SIFAT-SIFAT PENYALAAN BRIKET DENGAN MENGGUNAKAN SERBUK GERGAJIAN KAYU DENGAN COCO DUST SEBAGAI PEMANTIK - Petrus Patandung (Balai Riset Dan Standardisasi Industri Manado, 2016)
ABSTRACTThe properties of wood sawdust with coco dust for briquetting has been implemented. The purpose of this research product dinyalahkan briquettes obtained easily by using the